Leading student-centered coaching : building principal and coach partnership - Sweeney, Diane; Mausbach, Ann T. (Corwin, a SAGE Company, 2018)
"Student-Centered Coaching is a popular model of school-based coaching originated by author and consultant, Diane Sweeney. The core premise of Student-Centered Coaching is that coaches and teachers measure their respective impact based on student learning. In other words, the job of the coach isn't to "fix" teachers. Rather coaches work with teachers on (1) setting specific targets for students that are rooted in the standards and curriculum and (2) work collaboratively to ensure that these targets are met. A common obstacle to the effectiveness of school-based coaching initiatives is that, despite increased levels of investment for hiring and training coaches, we have failed to recognize the critical role of principal leadership in ensuring their success. The proposed title will introduce a concrete set of leadership moves for principals who seek to support a coaching effort in their own schools. When principals lack strategies for leading a coaching effort, they will encounter significant barriers to reaching their goal of positively impacting teaching and learning. This concrete and action-oriented guide will provide principals as well as district leaders with the background, practices, and tools for leading coaching efforts that result in increased learning for students and teacher alike"-- Provided by publisher